National de‐delegation in multi‐level settings: Independent regulatory agencies in Europe. Issue 1 (17th October 2022) - Rangoni, Bernardo; Thatcher, Mark
Abstract: National politicians in Europe have created independent regulatory agencies (IRAs) with significant powers over markets such as communications and energy. After delegation, they have engaged in institutional politicization of IRAs and undertaken numerous attempted or actual de‐delegations. Yet overall de‐delegation over the period 2000–2020 has been limited, as many de‐delegations have been abandoned, temporary or reversed, and also counterbalanced by extensions of IRA powers. The article examines different explanations for this pattern. It looks especially at Europeanization, which has operated through normative and particularly coercive mechanisms. EU coercion has involved threats of legal action, monitoring and enforcement of existing EU legal requirements, and EU legislation expanding IRA powers and protection. IRAs are more vulnerable to de‐delegation than trustee non‐majoritarian institutions because their position can be altered with simple legislative majorities. Yet even for such agents, the ability of national politicians to reverse delegation is constrained by multi‐level institutional settings.